Structural transition range of methane-ethane gas hydrates during decomposition below ice point. (15th September 2019) - Zhong, Jin-Rong; Sun, Yi-Fei; Li, Wen-Zhi; Xie, Yan; Chen, Guang-Jin; Sun, Chang-Yu; Yang, Lan-Ying; Qin, Hui-Bo; Pang, Wei-Xin; Li, Qing-Ping
Highlights: The dissociation of methane+ethane double hydrate samples was examined using in situ Raman spectroscopy. Hydrate structures were found to transfer from sI to sII over a methane composition of 50 mol–68 mol%. The occurrence time of structure transition is reduced with the increasing methane concentration. The mechanism of the structural transition occurring in gas hydrate decomposition was proposed. Abstract: The structural transition of methane-ethane gas hydrates is generally observed during the forming process; however, it has seldom been reported during the dissociation process. Study on the dissociation behavior of methane-ethane hydrate below ice point has important implications on gas storage and transportation. It was also be helpful for the natural gas hydrate production by depressurization in permafrost zones. The dissociation of a series of methane-ethane hydrate samples at atmospheric pressure and temperatures below ice point (272.15–269.15 K) was performed, and the influence of gas composition and temperature on the structural transition was examined using in situ Raman spectroscopy. The hydrate structures were found to transition from structure I to structure II over a methane composition range of 50–68 mol%. The hydrates remained as sI or sII type compounds, and no structural transition occurred during the dissociation when the methane content in methane-ethane gas mixture was decreased to a certain amount (<50 mol%) or increased to a higher value (≥70 mol%). Further investigation showed that the occurrence time of structural transition reduced with an increase in the methane concentration under the same decomposition temperature. Furthermore, hydrate dissociation was retarded upon decreasing the temperature in this temperature range (272.15–269.15 K). The mechanism of the structural transition occurring in gas hydrate decomposition was proposed.